Antioxidant activity, storage stability and in vitro release of epigallocatechin-3-gallate (EGCG) encapsulated in hordein nanoparticles. (15th September 2022) - Song, Hongdong; Wang, Qingyu; He, Aijing; Li, Sen; Guan, Xiao; Hu, Yawen; Feng, Siyi
Graphical abstract: Highlights: Hordein nanoparticles encapsulation had no effect on the antioxidant activity of epigallocatechin-3-gallate (EGCG). The storage stability of EGCG was significantly improved by hordein nanoparticles encapsulation. Release of EGCG from hordein nanoparticles was slowed down in the simulated gastric and intestinal fluids. Abstract: Hordein nanoparticles have been successfully fabricated to encapsulate EGCG. The present study aimed to investigate the effect of hordein nanoparticles encapsulation on antioxidant activity, storage stability and in vitro release of EGCG. The antioxidant activities of EGCG before and after encapsulation by hordein nanoparticles had no significant difference. The 28-day storage experiments indicated that EGCG-hordein nanoparticles had a good storage stability in terms of average diameter and zeta potential. Meanwhile, the stability of EGCG was significantly improved by hordein nanoparticles encapsulation. The remaining amount of encapsulated EGCG was 1.31-fold and 1.52-fold higher than that of free EGCG at 4 °C and 25 °C, respectively. The release study in the simulated gastric or intestinal fluids suggested that hordein nanoparticles could slow down the release of EGCG in the simulated gastric or intestinal fluids. These results showed that encapsulation of EGCG using hordein nanoparticles could be a promising approach to improve its stability.